PERANCANGAN DAN PEMBUATAN PLUG IN OBJECT 3DS MAX DENGAN MENGGUNAKAN PEMROGRAMAN MAXSCRIPT - Sholeh, Muhammad; Lestari, Uning; Arifuddin, Arham (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Software 3dsmax is application based on vector and three dimension. One of e-xamples from this software produces visualization and special effect. Software 3dsmax generally is used by a graphic artist/animator/illustrator and di-gital artist to get better composition, otherwise software 3dsmax giving opportunity to soft-ware user who has syntaxes composition skill as a programmer. In other word, 3dsmax provide software method such as point and click method, and scripting method. A programmer and animator are able produced the same three dimensions works by using 3dsmax software although they use different methods. Programmer does scrip-ting by using mini listener application as script editor whereas an animator use dynamic interface. The scripting method has prominent advantage, besides giving better performan-ce, it is an encapsulation process. Algorithm processes able to design and producing plug in which is can be use on software internal in 3dsmax application. Maxscript is internal programming software which is integrated with 3D Max ap-plication. It has different writing regulations with others programming language.